ANALISIS DINAMIKA PELATIHAN DALAM MENINGKATKAN DISIPLIN KERJA ORGANISASI HOCKEY DI JAKARTA TIMUR - Indriani, Agustina; Haholongan, Rutinaias; Anggraeni, Devina Nurul; Aprilia, Fadillah; Rahmawati, Rita; Zulfa, Iin Dana (SINERGI : Jurnal Riset Ilmiah, 2024)
Work discipline is an important factor that affects individual and team performance in an organization. This study aims to analyze the dynamics of training in improving the work discipline of hockey organizations in East Jakarta. The object of this research is the East Jakarta Zone within the scope of the hockey organization. The research method used is a quantitative approach with questionnaire survey techniques or interviews of hockey athletes in East Jakarta. The data collected were analyzed using descriptive methods to identify the effect of training on improving work discipline on hockey organizations in East Jakarta. The results of this study indicate that structured and sustainable training is able to improve athlete discipline, both in terms of compliance with rules, time management, and teamwork. In addition, training dynamics involving motivational approaches and consistent supervision from coaches play a significant role in building a culture of discipline among team members. The implication of this study is the importance of preparing training programs that not only focus on technical aspects, but also character development and work discipline to achieve optimal organizational performance.